Multiplex Detection of DNA Viruses in Transplant Recipients. (4th October 2017) - Tan, Susanna K; Shen, Peidong; Lefterova, Martina I; Sahoo, Malaya K; Odegaard, Justin; Pinsky, Benjamin; Scharfe, Curt
Abstract: Background: Viral infections are a significant cause of complications and death in solid organ and hematopoietic cell transplantation. Methods: We designed a multiplex sequencing assay (mVseq) that simultaneously detects 20 transplant-relevant DNA viruses from clinical samples. This method uses a single-tube multiplex PCR for the amplification of conserved virus genomic regions without the need for prior virus enrichment or host nucleic acid subtraction. Sequencing was performed using Illumina MiSeq and reads were aligned to a target sequence database. Analytical and clinical performance was evaluated using viruses in plasma spiked at different concentrations, and plasma ( n = 35) and non-plasma ( n = 12) samples including bronchoalveolar lavage fluid, cerebrospinal fluid, urine, and tissue from immunocompromised transplant recipients. Results: When compared with singleplex quantitative PCR (qPCR), mVseq showed 92% overall agreement (258/282 viral tests) and a kappa statistic of 0.77, mVseq demonstrated a sensitivity of 81% and specificity of 95%, with an area under the curve of 0.89. Sensitivity ranged from 62% to 100% and specificity from 82% to 100%, among specific viruses. Notably, mVseq identified previously unknown BK virus (BKV) and Human herpesvirus-7 (HHV-7) infections in various specimen types. BKV DNA detection was confirmed at titers >10, 000 copies/mL by qPCR in the plasma of 5 of the 27 HCT recipients and the 1 lung transplant recipient. A review of these cases revealed that some patients had documented dysuria, microscopic hematuria, and mild levels of acute kidney injury. In addition, HHV-7 was unexpectedly found in biopsy tissue in HCT recipients with clinical concern for gastrointestinal pathology. Conclusion: mVseq simultaneously detects multiple viruses in a variety of specimen types with comparable performance to singleplex qPCR. In addition to minimizing the need to order multiple single-target NAAT assays, this assay offers the potential to identify viruses not previously believed to be significant in immunocompromised transplant recipients. Disclosures: All authors: No reported disclosures.